P228 Referral Patterns and Outcomes For Patients Treated in a National Centre Specialising in Weaning From Invasive Mechanical Ventilation. (19th November 2012) - Banerjee, S; Pittman, M; Chadwick, R; Packer, D; Oscroft, N; Davies, M; Shneerson, J; Quinnell, T; Smith, I
Abstract : Introduction: With increasing evidence for the use of non-invasive ventilation (NIV) for acute COPD 1, a change in referral pattern to a national weaning unit was anticipated over time. We investigated the case mix and outcomes of patients referred to a unit specialising in weaning from invasive mechanical ventilation (IMV) over a 20 year period, comparing sequential 5-year cohorts. Methods: We undertook a retrospective analysis of 453 patient records referred to a national centre for weaning from IMV between January 1992 and December 2011. They were divided into four 5-year cohorts. Age on admission, gender, diagnostic group, length of stay on the weaning unit, survival, number successfully weaned from IMV and those requiring long term NIV at discharge were examined and compared between cohorts. Results: Figure 1 . Kaplan Meier plot of post discharge survival, comparing the four 5-year cohorts. A total of 453 patients were identified, 420 (93%) referred from other centres. Median age was 60.9 (IQR 49.6–70.2), 250 (55%) were male and median length of stay on the weaning unit was 27 days (IQR16–46). Thirty (7%) patients died before discharge. Of the survivors, 360 (79%) were weaned from IMV and 140 (31%) did not require any ventilatory support on discharge. No significant differences were found between the four cohorts in terms of age, gender, length of stay, proportions successfully weaned from IMV and requirement for NIV on discharge. There was no change in case mix, for example the proportions of patients with COPD were 18%, 23%, 26% and 22% across the four 5-year cohorts. Discussion: We did not identify any change in the referral pattern to our weaning unit, despite widespread use of NIV. With rates of 79% successfully weaned from IMV and a median survival of 29.2 months (IQR 20.8–37.7) referral to our weaning centre remains highly relevant for those receiving prolonged IMV and good outcomes can be anticipated. References: Ram FS, Picot J, Lightowler J, Wedzicha JA. Non-invasive positive pressure ventilation for treatment of respiratory failure due to exacerbations of COPD. Cochrane database 2004; (3): CD004104.